Algorithm for two-dimensional airfoil automatic structured mesh generation - Bitencourt, Pedro Henrique de Araújo [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The use of numerical methods to forecast aerodynamic phenomena has an important role in the industry, and the generation of meshes is an extremely important step for the expected results. This work seeks to develop the automatic generation of structured meshes through integration between the Python language and the open source software OpenFOAM, which interprets, through the blockMesh tool, a dictionary, then generates the structured mesh. The comparison with experimental data was used in order to verify the computational efficiency and accuracy of the generated structured meshes.

A utilização de métodos numéricos para previsão de fenômenos aerodinâmicos exerce papel de destaque na indústria, e a geração de malhas é uma etapa extremamente importante para os resultados esperados. Este trabalho busca desenvolver a geração automática de malhas estruturadas por meio de integração entre a linguagem Python e o software livre OpenFOAM, o qual interpreta, por meio da ferramenta blockMesh, um dicionário e assim gera a malha estruturada. A comparação com dados experimentais se faz necessária a fim de verificar a eficiência computacional e acurácia das malhas estruturadas geradas.
Algoritmo para geração automática de malha estruturada de aerofólios bidimensionais
Keywords: Python; blockMesh; OpenFOAM; CFD; Aerodinâmica; Malha estruturada